Assessment of Needs and Barriers to Continuing Professional Development among Nurses - Lim-Saco, Freslyn; Guino-o, Theresa A. (Silliman Journal, 2024)
Continuing Professional Development (CPD) is vital for nurses professional growth and advancement, ensuring high-quality, and safe patient care. This study explores the CPD needs and barriers among 51 nurses in Negros Oriental, using data from an electronic questionnaire after ethics clearance was obtained. Key CPD needs identified were Evidence-Based Practice, Promoting Healthy Workplace Culture, and Emergency Trauma Care. Major barriers included cost/registration fees, work schedules, and transportation. The study concludes that while nurses are keen on CPD and engagement in self-directed learning activities, financial, administrative, and socio-political support are needed. A well-tailored CPD program based on the knowledge of the needs and barriers enable nurses to stay updated with the latest advancements in healthcare thereby promoting high quality patient care, improvement in health outcomes, and contribute to functional multidisciplinary healthcare teams. It recommends similar studies across the Philippines to facilitate participatory and contextualized CPD implementation.